2017
DOI: 10.12965/jer.1732872.436
|View full text |Cite
|
Sign up to set email alerts
|

Exercise tolerance improves after pulmonary rehabilitation in pulmonary hypertension patients

Abstract: Pulmonary rehabilitation (PR) is part of the recommended management plan of pulmonary hypertension (PHTN) and is important to better quality of life and exercise tolerance. This study aimed at determining effectiveness of PR on exercise capacity. Retrospective chart analysis was conducted on patients referred to our PHTN clinic for PR. Patients who had PHTN diagnosed on right heart catheterization (defined by mean pulmonary artery pressure>25 mmHg) and completed a standardized 12-week PR program were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
1
9
0
Order By: Relevance
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Signifi cant improvement in chest excursions confi rm changes in breathing pattern suggesting better engagement of diaphragm during breathing after the program. The program emphasized promoting the engagement of diaphragm and "slow breath" to improve breathing pattern 34 and inspiratory muscle strength 35,36 that contributes to better exercise capacity 6,37 as well as more adaptive stress response (autonomic balance) 34,38 as were mentioned by the participants practicing the breathing exercises almost every day to manage daily activities. Because neither the pulmonary function nor level of oxygen consumption was assessed after the exercise program in the present study, the directly defi ned effects remain unclear and further studies are required.…”
Section: Improvement In Functional Status and Health Related Qolmentioning
confidence: 99%
“…Pulmonary hypertension is a cause of reduced exercise capacity; it may precede overt manifest pulmonary hypertension and is associated with a decreased life expectancy [28]. However, exercise training has been shown to be safe in these patients [11][12][13][14][15][16][29][30][31], and European guidelines recommend its use in experienced centers for patients who are clinically stable, on optimal pharmacological treatment [17,19].…”
Section: Discussionmentioning
confidence: 99%